Cooperation forwarding data gathering strategy of wireless sensor networks. (2017) - Chen, Ling; Liu, Lifang; Qi, Xiaogang; Zheng, Gengzhong
Limited energy and easy invalidation are the characteristics of WSNs (Wireless Sensor Networks). To prolong the lifetime of WSNs for building monitoring, an algorithm named CFDGSBRWB is proposed, which is a Cooperation Forwarding Data Gathering Strategy Based on Random Walk Backup in Wireless Sensor Networks. The algorithm consists of data backup based on random walk and cooperation forwarding data gathering by WBA (Wireless Broadcast Advantage). Simulation results show that CFDGSBRWB can reduce packet lost ratio and enhance fault-tolerance significantly under the condition of the insignificant increase of communication traffic, and is suitable for large-scale wireless sensor networks.